THE EFFECT OF CLOSED HOUSE CAGE DENSITY ON MICROCLIMATE OF BROILER CHICKENS - Zakaria, Jajat; Rifianda, Nabila Fara Dega; Widjastuti, Tuti; Mansyur, Mansyur; Hanifah, Muzdalifah Nur (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
The microclimate in the cage plays an important role in broiler productivity. Productivity is influenced by a good environment so that production will be maximized. The research was conducted in March-April 2023 in Pinggirsari Village, Arjasari District, Bandung Regency. The samples used were 52,500 broiler chickens of the Cobb CP 707 strain aged 0-32 days whose temperature, humidity, CO2 levels and NH3 levels in the cage were calculated. The cage used in this research is a closed house cage measuring 12x90 m divided into 6 partitions measuring 12 x 15 m, with each partition equipped with a feeding area and nipple drinker, fan feeder, baby chick feeder, and digital thermometer. The results of the study showed that cage density had a significant effect on temperature and levels of CO2 and NH3. Humidity had a real influence in the 4th and 5th weeks during maintenance on cage density. The average cage temperature is 25.17oC – 28.13oC, cage humidity is 70.41% - 82.24%, and CO2 levels are 594.13 ppm – 681.02 ppm. Density levels of up to 18 birds/m2 provide a good cage microclimate and are still optimal in industrial scale closed house cages. Keywords: broiler, cage density, microclimate